Knockdown of MVK does not lead to changes in NALP3 expression or activation. - Celsi, Fulvio; Piscianz, Elisa; Romano, Maurizio; Crovella, Sergio (J Inflamm (Lond), 2015)
BACKGROUND: Mutations in the Mevalonate Kinase gene (MVK) are causes of a rare autoinflammatory disease: Mevalonate Kinase Deficiency and its more acute manifestation, Mevalonic Aciduria. The latter is characterized, among other features, by neuroinflammation, developmental delay and ataxia, due to failed cerebellar development or neuronal death through chronic inflammation. Pathogenesis of neuroinflammation in Mevalonate Kinase Deficiency and Mevalonic Aciduria has not yet been completely clarified, however different research groups have been suggesting the inflammasome complex as the key factor in the disease development. A strategy to mimic this disease is blocking the mevalonate pathway, using HMG-CoA reductase inhibitors (Statins), while knock-out mice for Mevalonate Kinase are non-vital and their hemyzygous (i.e only one copy of gene preserved) littermate display almost no pathological features. FINDINGS: We sought to generate a murine cellular model closely resembling the pathogenic conditions found in vivo, by direct silencing of Mevalonate Kinase gene. Knockdown of Mevalonate Kinase in a murine microglial cellular model (BV-2 cells) results in neither augmented NALP3 expression nor increase of apoptosis. On the contrary, statin treatment of BV-2 cells produces an increase both in Mevalonate Kinase and NALP3 expression. CONCLUSIONS: MKD deficiency could be due or affected by protein accumulation leading to NALP3 activation, opening novel questions about strategies to tackle this disease.